Potential and Constraints of Public Debt as a Tool for Economic Growth - Monga're, Carolyne K.; Nyandemo, Dr. Samuel (International Journal of Economic Policy, 2021)
Purpose: The study sought to determine the potential and constraints of public debt as a tool for economic growth. Methodology: The study used secondary data for a time series of 1980 to 2012. Data used in this study is secondary and is extracted from the Government of Kenya Economic Surveys, Statistical Abstracts, World Development Indicators (WDI) of the World Bank and data from the public debt annual report of Kenya. Results: It was concluded that there was co integration among the long run variables. Results also indicated that in the long run, public domestic debt has a positive and significant relationship with GDP growth rate. Unique contribution to theory: The study recommends that government should borrow sustainably.It is also recommended that domestic debt should be kept to a manageable level.It is recommended that labour quality be improved through training and education as doing so would improve the GDP growth rate. Keywords: public debt ,economic growth, policy recommendations, research findings